2016
DOI: 10.1186/s12954-016-0092-3
|View full text |Cite
|
Sign up to set email alerts
|

Declining trends in the rates of assisted injecting: a prospective cohort study

Abstract: BackgroundAssisted injecting has been associated with increased risk of blood-borne infections, overdose, and other harms among people who inject drugs (PWID), particularly women. Given the changing availability of relevant harm reduction interventions in Vancouver, Canada, in recent years, we conducted a gender-based analysis to examine changes in rates and correlates of assisted injecting over time among active PWID.MethodsUsing data from a prospective cohort of PWID in Vancouver, we employed gender-stratifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 30 publications
(55 reference statements)
0
6
1
Order By: Relevance
“…We also found that receiving injection assistance alone was not significantly associated with either distributive or receptive syringe sharing. This finding differs significantly from prior studies where receiving injection assistance was associated with syringe sharing (Cheng et al, 2016;Lee et al, 2013;Pedersen et al, 2016;Robertson et al, 2010;, HIV infection, and HCV and HIV incidence (Lappalainen et al, 2015;Miller et al, 2002;Spittal et al, 2002). The lack of an association between receiving injection assistance and syringe sharing behaviors could be the result of three things.…”
Section: Discussioncontrasting
confidence: 97%
See 1 more Smart Citation
“…We also found that receiving injection assistance alone was not significantly associated with either distributive or receptive syringe sharing. This finding differs significantly from prior studies where receiving injection assistance was associated with syringe sharing (Cheng et al, 2016;Lee et al, 2013;Pedersen et al, 2016;Robertson et al, 2010;, HIV infection, and HCV and HIV incidence (Lappalainen et al, 2015;Miller et al, 2002;Spittal et al, 2002). The lack of an association between receiving injection assistance and syringe sharing behaviors could be the result of three things.…”
Section: Discussioncontrasting
confidence: 97%
“…Among PWID interactions, peer-to-peer injection or the practice of giving (provider) or receiving injection assistance (recipient) from another PWID, is an important contributor to health outcomes in this population. Both forms of peer-to-peer injection have been associated with infectious disease risk and other harms related to drug injection including syringe sharing (Carlson, 2000;Fairbairn et al, 2006;Friedman et al, 2002;Kral, Bluthenthal, Erringer, Lorvick, & Edlin, 1999;Lee et al, 2013;Pedersen et al, 2016;Wood et al, 2001), abscesses and soft tissue infections (Lee et al, 2013;Lloyd-Smith et al, 2008), drug overdose (Fairbairn, Small, Van Borek, Wood, & Kerr, 2010), and HIV incidence (Lappalainen, Kerr, Hayashi, Dong, & Wood, 2015;O'Connell et al, 2005;Spittal et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The majority of the evaluation papers were published between 2005 and 2011 (Figure ) and most were from Canada (Figure ). Since 2006, more papers described DCR/SIF clients or service operation . Also, after 2006, papers using qualitative methods have spiked including those focused on DCR clients or staff , and on other stakeholders .…”
Section: Resultsmentioning
confidence: 99%
“…In other BC population-based analyses, uninterrupted opioid agonist therapy (OAT) was associated with higher likelihood HCV treatment uptake among people who inject drugs after adjusting for sex, yet stimulant use disorder was negatively associated with treatment uptake [ 47 , 48 ]. Research has also demonstrated that gendered power dynamics contribute higher HCV exposure risk for women, such as being second on the needle, requiring help to inject, and needing to negotiate harm reduction with risk for violence [ 49 51 ]. Women with lived experience of HCV have highlighted that intersecting experiences of sexism, racism, and discrimination toward women who use injection drugs create significant barriers to accessing healthcare, including addiction treatment [ 27 , 43 ].…”
Section: Discussionmentioning
confidence: 99%